2021
DOI: 10.1021/acscatal.0c05656
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversification of Hapalindole and Fischerindole Natural Products via Cascade Biocatalysis

Abstract: Hapalindoles and related compounds (ambiguines, fischerindoles, welwitindolinones) are a diverse class of indole alkaloid natural products. They are typically isolated from the Stigonematales order of cyanobacteria and possess a broad scope of biological activities. Recently the biosynthetic pathway for assembly of these metabolites has been elucidated. In order to generate the core ring system, l-tryptophan is converted into the cis-indole isonitrile subunit before being prenylated with geranyl pyrophosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Similarly, a detailed understanding of the biosynthetic pathways leading to polyketides facilitated their production using microbial hosts . In this approach, pathways comprising multiple genes/biocatalysts are assembled to convert simple feedstocks into both the natural product and also analogues via mutasynthesis . However, these “biosynthetic” enzymes tend to be characterized by relatively low turnover rates and also narrow substrate scope, precluding their more general application as biocatalysts for target molecule synthesis.…”
Section: Biocatalysis In Drug Discoverymentioning
confidence: 99%
“…Similarly, a detailed understanding of the biosynthetic pathways leading to polyketides facilitated their production using microbial hosts . In this approach, pathways comprising multiple genes/biocatalysts are assembled to convert simple feedstocks into both the natural product and also analogues via mutasynthesis . However, these “biosynthetic” enzymes tend to be characterized by relatively low turnover rates and also narrow substrate scope, precluding their more general application as biocatalysts for target molecule synthesis.…”
Section: Biocatalysis In Drug Discoverymentioning
confidence: 99%
“…Next, we created a library of variously functionalized indole isonitrile/nitrile derivatives to test HpiC1 cyclase flexibility and its ability to create 11‐DMAC analogs. Previous work had shown that halogenated and oxygenated cis‐ indole isonitrile derivatives could be accepted by various Stig cyclases to produce both hapalindole and fischerindole compounds [19,20] . Derivatives were synthesized via a Horner‐Wadsworth‐Emmons (HWE) olefination on indole‐3‐carbaldehydes ( 6 a – n ) to afford cis ‐indole isonitrile substrates ( 1 a – n ) following the previously optimized procedure (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The indol-isonitrile derivatives often as a reaction intermediate or reactive material in organic chemistry (Hohlman et al 2021), such as synthesized biologically intriguing pyroglutamic acids (Isaacson et al 2007). But few studies focus on their own biological activity.…”
Section: Introductionmentioning
confidence: 99%